Assessment of ear length and low set ears in newborn infants. Issue 3 (June 1983) - Sivan, Y; Merlob, P; Reisner, S H
Abstract : In order to define normal values for ear length and position in the newborn infant, 198 (87 term and 111 preterm) infants were examined. In every case gestational age was determined chronologically and clinically. Ear length was measured from the superior to the inferior aspects of the ear. Using a horizontal line passing through the inner canthi of the eyes the portion of the ear above this line was measured, determining the position of the ear by its relation to total ear length. Normal values are presented by plotting the mean +/- 2 SD versus the gestational age. Small ears and low set ears are defined as values less than the mean -2 SD.